Financial Literacy as an Educational Competency for Creative Economy MSMEs - Sri Hardianti Sartika; Astri Srigustini; Allicia Deana Santosa; Kurniawan Kurniawan; Azizah Fauziyah (CV. Tripe Konsultan, 2025)
Financial literacy is a crucial competency for micro, small, and medium enterprises (MSMEs), particularly within the creative economy sector. This article aims to analyze the factors influencing financial literacy among MSME actors in West Java and discuss their implications for education and training. Using a quantitative approach, data were collected from 309 MSME operators in the culinary, fashion, and craft subsectors. The findings indicate that financial knowledge, understanding of financial concepts, personal financial management skills, and adaptive financial decision-making significantly and positively influence financial literacy. These results confirm that financial literacy is a multidimensional competency that should be strengthened through formal education, entrepreneurship training, and community empowerment programs. Integrating financial literacy education into entrepreneurship curricula and MSME training programs can support business sustainability and economic independence.